2013
DOI: 10.1002/chem.201300685
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Enantioselective Allylation of Ketimines by Using Palladium Pincer Complexes with Chiral Bis(imidazoline)s

Abstract: Get selective! Enantioselective allylation of ketimines derived from isatins by using chiral 1,3-bis(imidazolin-2-yl)benzene (Phebim)-Pd(II) complexes afforded products with good enantioselectivity (see scheme). The reaction was applied to a wide variety of ketimines. The obtained product can be converted to homoallylic amines and a spirocyclic amine without the loss of enantiopurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(48 citation statements)
references
References 109 publications
1
46
0
1
Order By: Relevance
“…The catalytic enantioselective allylation of isatin ketimines can be readily obtained using trimethoxyallylsilane 207 in the presence of the chiral palladium complex 208 (Scheme ) …”
Section: Spiroheterocyclic Derivativesmentioning
confidence: 99%
“…The catalytic enantioselective allylation of isatin ketimines can be readily obtained using trimethoxyallylsilane 207 in the presence of the chiral palladium complex 208 (Scheme ) …”
Section: Spiroheterocyclic Derivativesmentioning
confidence: 99%
“…1a) 7 . Other disclosures cover highly activated ketimines, including cyclic sulfonylimines and their reaction with potassium allyltrifluoroborates (with Rh-based catalysts) 8, 9 and isatin-derived N -Boc-ketimines and their reaction with allylsilanes (with Pd-based complexes and stoichiometric silver fluoride) 10 . Other approaches involve either enantiomerically pure ketimines 11, 12 or enantiomerically pure allyl reagents 13,14,15 .…”
mentioning
confidence: 99%
“…18 Nakamura et al reported an enantioselective allylation protocol to N-Boc ketimines 20 derived from isatins catalyzed by chiral Pd pincer-type catalyst 21 (Scheme 6). 19 The combined use of allyltrimethoxysilane and silver fluoride was essential for a smooth reaction, affording the allylated products 22 bearing a stereogenic α-tertiary amine on the oxindole core.…”
Section: Ketimines Derived From Isatinsmentioning
confidence: 99%